KONSEP TINDAK PIDANA PEMBUNUHAN BIASA DAN PEMBUNUHAN BERENCANA DALAM KATEGORI KEJAHATAN TERHADAP NYAWA - Fanny Tanuwijaya; Samuel Saut Martua Samosir; Wanda Eka Sri Masrita (Realism: Law Review, 2024)
The crime of murder is included in the category of crimes against life. The qualifications for the crime of murder consist several forms listed in Articles 338-350 of the KUHP. Broadly speaking, forms of murder are divided into two, the crime of ordinary murder and the crime of premeditated murder. These two forms of criminal acts of murder have differences, namely in the element of planning. The provisions of Article 338 of the Criminal Code explain murder in basic form, namely the intentional killing of another person. Meanwhile, Article 340 of the Criminal Code explains the deliberate taking of another person's life which is preceded by a plan. However, the meaning planning element in the Criminal Code is not explained in detail. This needs to be studied further regarding the differences between ordinary murder and premeditated murder. In analyzing this research, the author uses a normative juridical method with a statutory regulatory approach and a conceptual approach. The results of this research show that when it comes to planning elements, criminal events and the evidentiary process are seen which are linked to the theory of legal science doctrine applied by judges as a guide in making legal considerations in decisions